2016
DOI: 10.3390/su8090887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fertilization on Ramie (Boehmeria nivea L.) Growth, Yield and Fiber Quality

Abstract: Ramie (Boehmeria nivea L.) is one of the most important sources of natural fiber. The yield and fiber quality of ramie are affected by mineral nutrients, particularly nitrogen (N), phosphorus (P), and potassium (K). In the present study, we aimed to quantify the influence of N, P, and K fertilizers on growth, yield, and fiber quality of ramie. To this end, ramie plants grown under different fertilizer treatments (no fertilizer, N, P, K, NP, NK, PK, and NPK) were evaluated for differences in plant height, stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In the present study, fertilizer treatments that did not include N, such as the K, P, and PK treatments, produced shorter plants with less biomass and stem weight than the NK, NP, and NPK treatments. Ullah et al ., has also reported that treatment with combined NPK (150–75–150 kg ha −1 ) maximizes plant characteristics that affect ramie fiber yield 17 . Among the essential plant nutrients, N plays the most important role in improving agricultural production 17 , 18 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the present study, fertilizer treatments that did not include N, such as the K, P, and PK treatments, produced shorter plants with less biomass and stem weight than the NK, NP, and NPK treatments. Ullah et al ., has also reported that treatment with combined NPK (150–75–150 kg ha −1 ) maximizes plant characteristics that affect ramie fiber yield 17 . Among the essential plant nutrients, N plays the most important role in improving agricultural production 17 , 18 .…”
Section: Discussionmentioning
confidence: 94%
“…Ullah et al ., has also reported that treatment with combined NPK (150–75–150 kg ha −1 ) maximizes plant characteristics that affect ramie fiber yield 17 . Among the essential plant nutrients, N plays the most important role in improving agricultural production 17 , 18 . N application promotes the growth and fiber yield of ramie by increasing plant chlorophyll, soluble protein, and proline content; reducing MDA content; and enhancing gas exchange parameters and antioxidant enzyme activity 19 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ramie ( Boehmeria nivea ) is a plant source that has long, strong, durable fibers with high cellulose content, high antimicrobial resistance, and low cost . Therefore, ramie cellulose nanofibers have outstanding characteristics and a high potential to be used as a reinforcing material in starch‐based films.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, soil nitrogen and water are the most important factors affecting the growth of ramie and large amounts of N and water are required. Up to 280 kg/hm 2 of N would be used to maximize ramie yield [ 20 ] and the fiber yield could be decreased by more than 30% under N-deficit condition [ 21 ]. Compared to well-watered plants, the fiber yield, stem length, diameter, and bark thickness of ramie were decreased by 26.7%, 23.5%, 17.7%, and 19.7% under drought stress [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%